2022
DOI: 10.1073/pnas.2114336119
|View full text |Cite
|
Sign up to set email alerts
|

AhR promotes phosphorylation of ARNT isoform 1 in human T cell malignancies as a switch for optimal AhR activity

Abstract: Significance Nontoxic agonists and antagonists of the aryl hydrocarbon receptor (AhR) hold high therapeutic potential for treating autoimmune disease and cancer. However, AhR activation by different ligands can lead to opposing phenotypical outcomes in a cell- and tissue-specific manner. In this study, we demonstrate that proportional flux in the levels of aryl hydrocarbon receptor nuclear translocator (ARNT) isoforms 1 and 3 modulates AhR signaling in terms of amplitude and expression of distinct ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…AhRR and TiPARP function to provide negative feedback on AhR’s transcriptional activity, while SIN3A, typically regarded as a transcriptional repressor, was found to function as an essential co-activator for the transcription of CYP1A1 [ 67 ]. An additional mechanism fine-tuning the function of AhR was recently identified [ 68 ]. Bourner et al found that differential expression levels of ARNT isoforms altered the transcriptional activity of AhR, and ARNT isoform-dependent regulation of AhR was shown to be dependent on phosphorylation by the AhR target gene casein kinase 2 [ 68 ].…”
Section: Review Of Ahr Biology and Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…AhRR and TiPARP function to provide negative feedback on AhR’s transcriptional activity, while SIN3A, typically regarded as a transcriptional repressor, was found to function as an essential co-activator for the transcription of CYP1A1 [ 67 ]. An additional mechanism fine-tuning the function of AhR was recently identified [ 68 ]. Bourner et al found that differential expression levels of ARNT isoforms altered the transcriptional activity of AhR, and ARNT isoform-dependent regulation of AhR was shown to be dependent on phosphorylation by the AhR target gene casein kinase 2 [ 68 ].…”
Section: Review Of Ahr Biology and Signalingmentioning
confidence: 99%
“…An additional mechanism fine-tuning the function of AhR was recently identified [ 68 ]. Bourner et al found that differential expression levels of ARNT isoforms altered the transcriptional activity of AhR, and ARNT isoform-dependent regulation of AhR was shown to be dependent on phosphorylation by the AhR target gene casein kinase 2 [ 68 ].…”
Section: Review Of Ahr Biology and Signalingmentioning
confidence: 99%
“…However, compared to the AHR, less is known about the regulation of ARNT. ARNT is expressed in most cells as two isoforms that vary in the presence or absence of a 45 amino acid segment [ 6 ]. Casey Wright from the University of Texas at Galveston, USA, reported that in human T cells, the level of AHR transcriptional activity is dependent on which isoform of ARNT heterodimerized with the AHR.…”
Section: Sessions and Presentationsmentioning
confidence: 99%
“…He found, using transcriptomics and molecular analyses, that a low intracellular ARNT isoform 1:3 ratio enhances AHR responsiveness to ligand activation but abrogates NF-kB-inducing stimuli. Activation of primary CD4 + T cells promoted a physiological increase in the ARNT isoform ratio that favors NF-κB signaling, which is further enhanced by suppression of AHR [ 6 ]. Karin Loser from the University of Oldenburg, Oldenburg, Germany, presented work on experimental autoimmune encephalomyelitis (EAE), a mouse model mimicking aspects of human multiple sclerosis.…”
Section: Sessions and Presentationsmentioning
confidence: 99%
“…1D). Among them, ELF1, IRF3, ZNF410, and ARNT may promote the development of inflammation or senescence [42][43][44][45]. ATF7 not only plays a repressive role in innate immunity [18], but also responds to intrinsic and extrinsic stresses [17], and thus was chosen as the candidate gene (Fig.…”
Section: Centenarians Display Lower Inflammation With Possible Atf7 I...mentioning
confidence: 99%